On the sensitivity of Southern Ocean sea ice to the surface freshwater flux: A model study - Marsland, SJ; Wolff, J (2001)
The Hamburg Ocean Primitive Equation model is used to study the response of the Southern Ocean's vertical stability and sea ice cover to variations in the prescribed surface freshwater flux (SFWF). The model is used to investigate the response of the coupled ocean-sea ice system to a number of SFWF climatologies and to changes in the mean surface air temperature of the Southern Hemisphere. The modeled sea ice cover is very sensitive to the SFWF. In particular, a large-scale open ocean polynya develops in the Weddell Sea when the SFWF in that region falls below a critical value of ∼35 cm yr-1. In terms of the oceanic heat flux (OHF) to the base of the sea ice, decreasing the SFWF by 10 cm yr-1 has roughly the same effect as an increase of 2°C in the surface air temperature, with both of these changes acting to increase the Southern Ocean's mean annual OHF of ∼23 W m-2 by ∼10%. Coupled ocean-atmosphere models of transient climate change due to greenhouse warming predict an increase in both surface air temperature and SFWF over the Southern Ocean sea ice zone. Because the sensitivity of the sea ice extent and volume, and of the OHF, to increasing surface air temperature is opposite to that of increasing SFWF, these effects can be expected, at least partially, to offset each other. Copyright 2001 by the American Geophysical Union.